2006
DOI: 10.1128/iai.74.3.1505-1515.2006
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Enhancement of Virulence by Enterotoxigenic and Enteropathogenic Escherichia coli

Abstract: Enterotoxigenic Escherichia coli (ETEC) and enteropathogenic E. coli (EPEC) are common causes of diarrhea in children in developing countries. Dual infections with both pathogens have been noted fairly frequently in studies of diarrhea around the world. In previous laboratory work, we noted that cholera toxin and forskolin markedly potentiated EPEC-induced ATP release from the host cell, and this potentiated release was found to be mediated by the cystic fibrosis transmembrane conductance regulator. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 59 publications
(59 reference statements)
0
28
0
Order By: Relevance
“…The heat-stable toxin (ST) is less well characterized for its immunomodulating properties than are LT and CT. Dual infections of children in developing countries with ETEC and enteropathogenic E. coli (EPEC) have been observed (10,26), and recent studies have shown that purified ST or crude extracts of ETEC can enhance the virulence of EPEC by use of laboratory-based in vitro assay systems (8). This suggested a molecular basis for the role of ST in causing an increased severity of disease in EPEC diarrhea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heat-stable toxin (ST) is less well characterized for its immunomodulating properties than are LT and CT. Dual infections of children in developing countries with ETEC and enteropathogenic E. coli (EPEC) have been observed (10,26), and recent studies have shown that purified ST or crude extracts of ETEC can enhance the virulence of EPEC by use of laboratory-based in vitro assay systems (8). This suggested a molecular basis for the role of ST in causing an increased severity of disease in EPEC diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, for toxinmediated enteric infections, robust responses are needed to overcome the effect of the toxins, for achieving protective efficacy for these major pathogens, and to formulate a widerange global vaccine (8). Since the presence of O-blood-group antigen was previously found to be associated with susceptibility to cholera (18) and to be associated with the magnitude of immune responses generated after vaccination (21), we analyzed the effect of this antigen on the immune responses seen for our three study groups.…”
Section: Discussionmentioning
confidence: 99%
“…ATP is subsequently degraded to adenosine, which is able to stimulate a chloride secretory response (8). LT (and STa) had previously been shown to potentiate the release of ATP from EPECinfected cells (7) and may increase disease severity in mixed EPEC/ETEC infections (7).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Crane et al identified that the virulence of EPEC prototype strain E2348/69 was enhanced by the release of ATP in the presence of heat-stable toxin (STa) produced by an ETEC isolate (5). Interaction of isolates from these two pathovars has also been previously noted in epidemiological studies (52).…”
mentioning
confidence: 97%